Kehidupan Sosial Tokoh Utama Pada Novel Hujan Karya Tere Liye - Nadjwa Salshabilla Humayra; Jumadi, Jumadi; Dwi Wahyu Candra Dewi (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research aims to describe the social values in the Novel Rain by Tere Liye with the main focus on the female character named Lail. The formulation of the problem in this research is what are the social values in the Novel Rain by Tere Liye. This research uses qualitative methods and descriptive research with a literary sociology approach. The data source for this research is the Novel Rain by Tere Liye. The data in this research was obtained from descriptions, sentences, dialogue excerpts. Based on the data findings, there are three aspects of social values, namely: 1) Love/affectionate values, 2) Responsibility/accountability, and 3) Harmony in Life/harmony of life. Researchers obtained the most data on the aspect of love/affection, the character Lail has the character of being patient, compassionate and caring towards others.